Cyclooxygenase‐2, prostaglandin E2 glycerol ester and nitric oxide are involved in muscarine‐induced presynaptic enhancement at the vertebrate neuromuscular junction. (9th August 2013) - Lindgren, Clark A.; Newman, Zachary L.; Morford, Jamie J.; Ryan, Steven B.; Battani, Kathryn A.; Su, Zheng
Key points The synapse between a nerve and muscle, called the neuromuscular junction (NMJ), undergoes a biphasic modulation, a decrease followed by an increase, when muscarinic acetylcholine receptors are continuously activated. The initial depression is caused by the endocannabinoid 2‐arachidonylglycerol (2‐AG), which is synthesized in and released from the muscle; 2‐AG then activates cannabinoid receptors on the presynaptic nerve. In the work presented here, we explored the mechanism responsible for the delayed enhancement, uncovering a role for the enzyme cyclooxygenase‐2 and locating it in the glial cells at the NMJ called perisynaptic Schwann cells (PSCs) where it converts 2‐AG into the glycerol ester of prostaglandin E2. These results reveal a complex mechanism for regulating neurotransmitter release that involves the nerve, muscle and PSCs (i.e. the tripartite synapse) and may serve to ensure reliable neuromuscular transmission during periods of intense or long‐term activity. Abstract Previous work has demonstrated that activation of muscarinic acetylcholine receptors at the lizard neuromuscular junction (NMJ) induces a biphasic modulation of evoked neurotransmitter release: an initial depression followed by a delayed enhancement. The depression is mediated by the release of the endocannabinoid 2‐arachidonylglycerol (2‐AG) from the muscle and its binding to cannabinoid type 1 receptors on the motor nerve terminal. The work presented here suggests that the delayed enhancement of neurotransmitter release is mediated by cyclooxygenase‐2 (COX‐2) as it converts 2‐AG to the glycerol ester of prostaglandin E2 (PGE2‐G). Using immunofluorescence, COX‐2 was detected in the perisynaptic Schwann cells (PSCs) surrounding the NMJ. Pretreatment with either of the selective COX‐2 inhibitors, nimesulide or DuP 697, prevents the delayed increase in endplate potential (EPP) amplitude normally produced by muscarine. In keeping with its putative role as a mediator of the delayed muscarinic effect, PGE2‐G enhances evoked neurotransmitter release. Specifically, PGE2‐G increases the amplitude of EPPs without altering that of spontaneous miniature EPPs. As shown previously for the muscarinic effect, the enhancement of evoked neurotransmitter release by PGE2‐G depends on nitric oxide (NO) as the response is abolished by application of either NG‐nitro‐l‐arginine methyl ester (l‐NAME), an inhibitor of NO synthesis, or carboxy‐PTIO, a chelator of NO. Intriguingly, the enhancement is not prevented by AH6809, a prostaglandin receptor antagonist, but is blocked by capsazepine, a TRPV1 and TRPM8 receptor antagonist. Taken together, these results suggest that the conversion of 2‐AG to PGE2‐G by COX‐2 underlies the muscarine‐induced enhancement of neurotransmitter release at the vertebrate NMJ.